Darmasiswa Awardee’s Perceptions on the Implementation of Bahasa Indonesia bagi Penutur Asing (BIPA) Class - Dewangga, Vigo; Binarkaheni, Suyik; Ihsan, Pramudana; Himphinit, Musakkid (Politeknik Negeri Jember, 2024)
Politeknik Negeri Jember offers several scholarship programs that provide opportunities for foreign students to pursue degree and non-degree education in Indonesia. One such scholarship is the Darmasiswa program, which aims to enhance the awardees' knowledge of Indonesian culture and language through the Bahasa Indonesia Bagi Penutur Asing (BIPA) class. To achieve this goal, the campus collaborates with the Language Center and International Office to organize the class. The program is conducted in three phases: 1) preparation, 2) implementation, and 3) evaluation. The evaluation phase is crucial for improving the program's quality. This study aims to describe the evaluation phase by analyzing the awardees' perceptions of the program. A questionnaire was used as the primary instrument, followed by interviews for confirmation. The results indicate that awardees generally have a positive perception of the program, as evidenced by their enthusiasm for the class. These findings are expected to help maintain and improve the quality of the BIPA class.